Remaking the state: education and religious reform in Bavaria under Maximilian IV Joseph, 1796-1808 - McCallister, Stephanie (Kansas State University, 2014)
During the late eighteenth and early nineteenth centuries, Bavaria embarked on an ambitious program of reform that fundamentally altered the Bavarian state and society. The men responsible for such dramatic changes were Maximilian IV Joseph, the last Elector and first King of Bavaria, and Maximilian Joseph Graf von Montgelas, his closest advisor. Both Max Joseph and Montgelas sought to modernize their government through the removal of feudal remnants and increased participation of the kingdom’s subjects. Reforms in education and religion were central to this endeavor. Education reforms developed the skills necessary for improving society, increasing the state’s prosperity, and instilling a sense of loyalty to the Bavarian king. Religious reforms helped to eliminate prejudice and better integrate the Protestant and Catholic subjects into Bavarian society, particularly in the areas Bavaria gained during the Napoleonic wars. By maintaining a balance between preserving loyalty to the king and increasing participation in the state’s modernization, the Bavarian monarch hoped to reap the benefits of enlightened reform and prevent revolution. Previous histories of reform during the Napoleonic Era have focused on Austria and Prussia but Bavaria deserves attention as well. There is a pendulum-like quality to Bavarian history that swings between reform and reaction. In 1799 when Max IV Joseph and Montgelas came to Munich, reform and self-preservation in the face of the French Revolution and Napoleon, as well as the changing face of the Holy Roman Empire, served as the impetus for reform. Reform in the early nineteenth century allowed the Bavarian bureaucrats to strengthen the power of the king and increase the wealth of the state. Through a careful analysis of the reform edicts, personal papers of Montgelas, and statements from outside commentators, a clearer picture of reform in Bavaria can be pieced together and the true impact of reform during the Napoleonic Period can be seen; reform that made the Bavaria of Max Joseph almost unrecognizable from the Bavaria of his predecessor.
Keywords: Bavaria; Education; Religion; Reform; Napoleonic Period; European History (0335)